Single-Stage Multiple-Ligament Knee Reconstructions for Sports-Related Injuries: Outcomes in 194 Patients. Issue 11 (September 2019) - LaPrade, Robert F.; Chahla, Jorge; DePhillipo, Nicholas N.; Cram, Tyler; Kennedy, Mitchell I.; Cinque, Mark; Dornan, Grant J.; O'Brien, Luke T.; Engebretsen, Lars; Moatshe, Gilbert
Background: Outcomes after sports-related multiple-ligament knee reconstructions are limited. Purpose: To evaluate outcomes after single-stage surgical treatment of sports-related multiple-ligament knee injuries and to compare outcomes after anterior cruciate ligament (ACL)–based and posterior cruciate ligament (PCL)–based multiple-ligament knee reconstructions. Study Design: Case series; Level of evidence, 4. Methods: Skeletally mature patients with at least 2 major knee ligaments torn during a sporting activity that required surgery with a minimum of 2 years' follow-up were included. The Lysholm score, Tegner activity scale, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and 12-Item Short Form Health Survey Physical Component Summary were collected preoperatively and at a minimum of 2 years' follow-up. Clinical data, including range of motion and knee stability, were also recorded at final follow-up. Results: A total of 276 patients with multiple-ligament knee injuries incurred during sport participation from 2010 to 2016 were identified. Of the 276 patients, 194 (70.5%) had complete follow-up at a mean 3.5 years (range, 2-8 years). There was a significant improvement in all outcome scores as compared with the preoperative scores ( P < .001 for all scores). The median (first and third quartiles) Tegner activity score improved from 1 (0, 2) preoperatively to 6 (4, 7) postoperatively. Significant improvements were from 41 (22, 57) to 90 (78, 95) and 44 (24, 60) to 3 (1, 8) for median Lysholm and WOMAC scores, respectively. There was no significant difference in postoperative outcome scores between patients treated in the acute and chronic phases. Furthermore, there was no significant difference between PCL- and ACL-based multiple-ligament knee injuries. Eighteen (9.3%) patients developed arthrofibrosis requiring reintervention surgery. Conclusion: These results demonstrated that single-stage anatomic-based knee ligament reconstructions with immediate postoperative rehabilitation in the setting of sports-related multiligament injuries yielded significantly improved outcomes irrespective of the ligament injury pattern. In addition, there was no difference in outcomes between ACL- and PCL-based injuries in the setting of sports-related multiligament injuries.